The effect of the web-based psychosocial health promotion program on the burden of care in family caregivers of patients with chronic mental disorders - Fatemeh Lohrasebi; Jahangir Maghsoudi; Mousa Alavi; Mohammad Akbari (Wolters Kluwer Medknow Publications, 2023)
Background: Family members of Chronic Mental Disorders (CMD), who are responsible for patient care, face many physical, psychological, and social problems which make them face the burden of care. This study aimed to investigate the effect of a psychosocial health promotion program on the care burden of family caregivers of patients with CMD. Materials and Methods: This is a quasi-experimental study that was conducted in two intervention and control groups in the form of pretest and posttest. This study was performed on 67 family caregivers of patients with CMD in Farabi and Noor centers in Isfahan, Iran. Participants in this study were randomly divided into two intervention and control groups. Data from the intervention and control groups were collected in two stages, before and after the intervention by demographic information form and Zarit burden questionnaire. The intervention group received a web-based psychosocial health promotion program in eight sessions in 4 weeks. At the end of the intervention, the Zarit questionnaire was completed by the intervention and control groups. Results: The mean score of care burden between the intervention and control groups was not statistically significantly different before the implementation of the program (p = 0.534). But after the intervention, the mean score of care burden was significantly different between the two groups (t65 = 3.43, p = 0.001). Conclusions: This study provides evidence for the benefits of web-based psychosocial health promotion program in reducing the perceived care burden of the caregiver of CMD.